Sandfly (Diptera: Psychodidae) distributiοn in Northern Greece - Karanis, P.; Frank, C.; Schmalle, H.; Naucke, T. J.; Jorden, U.; Metallinou, C.; Haralabidis, S.; Maier, W. A.; Seitz, H. M.; Himonas, C. (ENTOMOLOGIA HELLENICA, 2000)
This study is a part of investigations on leishmaniasis vectors which began in 1992. Sandflies were collected in different areas of Kassandra, Sithonia and Athos and in several biotopes of the Xanthi district in Thrace. A total of 811 sandflies were caught using oil-traps in peridomestic sites in the town of Neos Marmaras in 1992, and 4264 specimens were collected by CDC miniature light traps in different parts of Chalkidiki in 1993. Similarly 3465 specimens were collected in Xanthi in 1996. Eight species of sandflies were identified: Phlebotomus (Larroussius) neglectus Tonnoir 1921, P. (L.) tobbi Adler et al. 1930, P. (L.) perfiliewi Parrot 1930, P. (Paraphlebotomus) sergenti Parrot 1917, P. (Adlerius) simici Nitzulescu & Nitzulescu 1931, P. (Phlebotomus) papatasi Scopoli 1786, Sergentontomyia minuta Rondani 1843 and S. dentata Sinton 1933. The roles played in the transmission of leishmaniasis by different species of sandflies is discussed.